2013
DOI: 10.1111/ggi.12048
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of lower urinary tract symptoms in middle‐aged and elderly Japanese

Abstract: The results showed that the severity of LUTS in Japan was related to aging. The prevalence of LUTS with I-PSS ≥ 8 in Japan is similar to that in other countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…[1][2][3][4][5][6] The ICI recommended the use of the ICIMaleSF questionnaire for men and ICIFemaleSF for women on assessing LUTS; however, they could contain too extensive or variable questions. [7][8][9] The CLSS questionnaire was reported by Homma et al in 2008.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] The ICI recommended the use of the ICIMaleSF questionnaire for men and ICIFemaleSF for women on assessing LUTS; however, they could contain too extensive or variable questions. [7][8][9] The CLSS questionnaire was reported by Homma et al in 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Another important problem in geriatric urology is LUTS. In contrast to cancer, there are no racial differences in the incidence of LUTS . Recently, “frailty” has become a commonly used medical term in gerontology.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to cancer, there are no racial differences in the incidence of LUTS. [41][42][43][44] Recently, "frailty" has become a commonly used medical term in gerontology. Frailty is defined as a state of vulnerability that has been conceptualized as a biological syndrome of decreased reserve or resistance to stressors, which results in adverse outcomes, such as disability, institutionalization and mortality.…”
Section: Subspecialties Of Japanese Urologistsmentioning
confidence: 99%
“…The author reported frequency, urgency and nocturia in 73.5%, 67.3% and 97.3% subjects respectively. Other studies have reported symptoms leading to LUTS as; urgency 13.1%, 15 nocturia 48.6%,16 frequency 12%,22 poor stream 8.5%,22 incomplete emptying of bladder 27%, 13 urge incontinence 25.8%, 23 terminal dribbling 58.1%, 24 and hesitancy is 8%.25 In the study of Sunter AT et al 26 , nocturia (71.7%) was also found to be the most prevalent lower urinary tract symptom, followed by urination frequency as 50.8%, incomplete emptying of the bladder as 44.3%, hesitancy of urination as 41.7%, poor urine flow as 41.6%, intermittency of urination as 37.5% and urgency of urination as 27.8%.…”
Section: Methodsmentioning
confidence: 97%
“…It has substantial economic burden on health care system. Symptoms leading to LUST have been reported as; urgency 13.1%, 10 nocturia 48.6%, 11 frequency 12%, 12 poor stream 8.5%, 12 incomplete emptying of bladder 27%, 13 urge incontinence 25.8%, 14 terminal dribbling 58.1%, 15 and hesitancy is 8%. 16 LUTS are assessed by International Prostate Symptom score (IPSS).9 Correct determination of prevalence of lower urinary tract symptoms may help the health service provider to plan appropriate management strategies.…”
Section: Introductionmentioning
confidence: 99%